The Internalization of Islamic Values in English Language Teaching - Zainuddin; Gumarpi Rahis Pasaribu (Rahis Cendekia Indonesia, 2025)
The integration of Islamic values into English language teaching has become an important issue in Islamic educational institutions, particularly in contexts where English is taught as a foreign language. English language instruction is often perceived as focusing primarily on linguistic skills, with limited attention to moral and spiritual dimensions. This condition raises concerns regarding the need to balance language competence with character and value education. Therefore, internalizing Islamic values in English language teaching is essential to ensure that students develop not only communicative abilities but also strong moral and spiritual foundations. This study aims to explore the internalization of Islamic values in English language teaching and to examine how these values are implemented in classroom practices. Employing a qualitative research design, the study was conducted in an Islamic-based educational institution where English is taught as a compulsory subject. The participants consisted of English teachers selected through purposive sampling. Data were collected through classroom observations, semi-structured interviews, and document analysis, including lesson plans and teaching materials. The data were analyzed using an interactive model involving data reduction, data display, and conclusion drawing to identify recurring themes related to the integration of Islamic values. The findings reveal that Islamic values are internalized in English language teaching through the integration of moral principles into learning objectives, teaching materials, classroom activities, and teacher–student interactions. Values such as honesty, discipline, responsibility, respect, cooperation, and politeness are consistently emphasized during the learning process. Teachers employ Islamic-contextualized materials, such as reading texts and dialogues containing moral messages, and reinforce values through daily classroom routines, including greetings and reflective practices. Teacher modeling and communicative behavior also play a crucial role in strengthening value internalization. Despite the positive implementation, the study identifies several challenges, including limited availability of English teaching materials that explicitly integrate Islamic values and varying levels of teacher preparedness in applying value-based instruction. Nevertheless, the integration of Islamic values is perceived to enhance students’ motivation, engagement, and character development without hindering language acquisition. In conclusion, the internalization of Islamic values in English language teaching contributes to holistic education by combining linguistic competence with moral and spiritual growth. The study recommends greater institutional support, teacher training, and the development of value-based English teaching resources to strengthen the effectiveness of this integrative approach.